Geographic information system-based approaches for evaluating CO2 storage in Kalimantan basins, Indonesia - Susantoro, Tri Muji; Sugihardjo, Sugihardjo; Suliantara, Suliantara; Widarsono, Bambang; Usman, Usman; Setiawan, Herru Lastiadi; Romli, Mohamad; Sukarno, Panca W.; Nurkamelia, Nurkamelia; Suhartono, Rudi (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
To achieve the energy transition towards more environmentally friendly energy, various approaches must be taken, one of which is CO2 source-to-sink matching. A basin evaluation study has been carried out through classifying, weighting, and scoring in the geographic information system (GIS) for screening and ranking basins for CO2 storage on the island of Kalimantan, Indonesia. The region covers 13 sedimentary basins that have the potential to serve as CO2 sinks. As many as 21 parameters have been analyzed through classification and weighting using a pairwise comparison matrix method to produce scores and ranks for each basin. The results show that the Kutai, Tarakan, and Barito basins are the top three basins for CO2 storage potential. Singkawang, Nangapinoh, Pangkalanbun Utara, and Embaluh Selatan basins have been found to have the lowest sink potential.